1999
DOI: 10.1097/00000478-199903000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mutations of Ki-RAS and p53 Immunoreactivity in Borderline and Malignant Epithelial Ovarian Tumors

Abstract: Ovarian tumors of low malignant potential ("borderline tumors") have been proposed variably to represent a distinctive type of malignancy, precursors of frank ovarian malignancy, or a nonmalignant process. We analyzed 81 malignant and 39 borderline ovarian tumors for p53 immunoreactivity and alterations in codon 12 of Ki-RAS in order to correlate these alterations with tumor and cell type. Diffuse p53 immunoreactivity was significantly more prevalent among malignant (36 of 81, 44%) than among borderline (3 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 24 publications
6
56
0
1
Order By: Relevance
“…Most studies have shown a high and increasing frequency of KRAS mutations in mucinous cystadenomas, borderline tumors and carcinomas, ranging from 33 to 86%. 47,70,72,75,87,88 Several groups 75,87,88 have noted similar KRAS mutation patterns in benign, borderline and malignant mucinous areas within the same neoplasm, which suggests that KRAS mutation is an early event in mucinous tumorigenesis. It has also been noted that the rate of TP53 mutations is lower in mucinous borderline tumors than mucinous carcinomas (13 vs 40%).…”
Section: Molecular Genetic Datamentioning
confidence: 97%
See 2 more Smart Citations
“…Most studies have shown a high and increasing frequency of KRAS mutations in mucinous cystadenomas, borderline tumors and carcinomas, ranging from 33 to 86%. 47,70,72,75,87,88 Several groups 75,87,88 have noted similar KRAS mutation patterns in benign, borderline and malignant mucinous areas within the same neoplasm, which suggests that KRAS mutation is an early event in mucinous tumorigenesis. It has also been noted that the rate of TP53 mutations is lower in mucinous borderline tumors than mucinous carcinomas (13 vs 40%).…”
Section: Molecular Genetic Datamentioning
confidence: 97%
“…[38][39][40][41][42][43][44][45][46][47] It has also been demonstrated that loss of BRCA1 or BRCA2 function by a variety of mechanisms is present in the majority of both sporadic and hereditary high-grade serous and endometrioid carcinomas. 48,49 Boyd and coworkers 36 36,37 demonstrated the same mutation in the carcinoma and the adjacent normal or atypical epithelium in a small number of cases.…”
Section: High-grade Serous Carcinomasmentioning
confidence: 99%
See 1 more Smart Citation
“…KRAS mutations are the most common genetic event in 50% of mucinous borderline tumors and in 60% of primary MuOCs 8, 9, 10, 11, 1213.…”
mentioning
confidence: 99%
“…Grade not determined (64%) 33/46 (72) (Gadducci et al, 2006) 47/71 (66) (Havrilesky et al, 2003) 16/26 (62) (Caduff et al, 1999) 14/31 (45) (Fujita et al, 1994) 11/20 (55) (Henriksen et al, 1994) 18/23 (78) (Renninson et al, 1994) 31/42 (74) (Dogan et al, 2005) 73/126 (58) (Eltabbakh et al, 1997) Clear cell (8%) 6/38 (17) (Ho et al, 2001) 0/4 (0) (Otis et al, 2000) 1/12 (8) (Caduff et al, 1999) Endometrioid (45%) 5/15 (33) (Dogan et al, 2005) 7/13 (54) (Henriksen et al, 1994) 13/27 (48) (Caduff et al, 1999) Mucinous (19%) 1/12 (8) (Dogan et al, 2005) 3/12 (25) (Renninson et al, 1994) 3/11 (27) (Henriksen et al, 1994) 3/21 (14) (Caduff et al, 1999) (Hashiguchi et al, 2001) 70/117 (60) (Saegusa et al, 2001) 28/82 (34) (Havrilesky et al, 2001) 9/73 (12) (Tachibana et al, 2003) 23/107 (21) (Hashiguchi et al, 2001) 60/134 (45) (Bali et al, 2004) RB Homozygous mutation (9%) 1/24 (4) (Sasano et al, 1990) 2/15 (13) Loss of or aberrant expression (19%) 2/25 (8) (Dodson et al, 1994) 2/26 (8) (Kim et al, 1994) 3/22 (14) (Taylor et al, 1995) 7/34 (21) (Niemann et al, 1998) 2/59 (3) (Kusume et al, 1999) 5/46 (11) (Hashiguchi et al, 2001) 7/9 (78) (Gras et al, 2001) 10/84 (12) (Havrilesky et al, 2001) 1/78 (1) (Konstantinidou et al, 2003) 28/134 (21) (Bali et al, 2004) 12/107 (37) (Hashiguchi et al, 2...…”
mentioning
confidence: 99%